Comparative Analysis of President Soeharto and Kim Dae Jung's Policies in Overcoming the 1997 Economic Crisis based on Small Theory and Idiosyncratic Theory - Putri Jasmine Surapati; Nada Nur Maulidina; Fayza Maritza Putri Agustono; Hilda Ferira Pohan (UIN Sunan Gunung Djati, 2021)
The 1997 economic crisis was a situation in which the Asian economy experienced a drastic decline which was triggered by Thai finance. At that time Thailand, burdened by huge foreign debt, decided to develop the Baht currency after attacks by currency speculators on the country's foreign reserves. This monetary shift was aimed at stimulating export earnings but this strategy actually had a bad impact. This has had the effect of transmitting to several countries in other Asian regions, such as South Korea and Indonesia. In responding to the formulation of this phenomenon, South Korea and Indonesia have their own policies to overcome the 1997 Economic Crisis.Thus, in order to understand the decision-making process in foreign policy, a level of analysis is needed, namely using idiosyncratic theory and small theory. Using a qualitative approach, this research generates ideas to understand the background to the policy process it created to address the issue of the 1997 Economic Crisis.